Safety evaluation of Sri Lankan Piper betle leaf extracts in rats - Arambewela, L.S.R.; Arawwawala, L.D.A.M.; Ratnasooriya, W.D. (My University, 2003)
The aim of this study was to evaluate the safety profile of cold ethanolic extract (CEE) and hot water extract (HWE) of Sri Lankan Piper betle Linn, leaves (Family: Piperaceae).The extracts were orally administrated to rats for 42 consecutive days. These rats were monitored for overt signs of toxicity, stress, morbidity, aversive behaviors or mortality throughout the experiment. Weight gain, food and water intake were determined weekly. On day 1 post treatment, the rats were sacrificed, blood collected and organs were weighed. The results showed that both extracts were well tolerated in terms of % weight gain, food and water intake, morbidity, aversive behaviors, mortality, blood haematology, serum analysis and organ weights except the weight of the spleen, which suggested lymphoproliferative activity